A Case Study on Customer Satisfaction towards Service Quality of Front Office Staff at Radisson Blu Hotel [Delhi NCR (Global Journal of Management and Business Research, 2022)
Guest satisfaction is important because it gives us business and if they are satisfied then it increases the chances of a guest returning to do more business. It generally means how the guest is satisfied with the company products and service. The hospitality industry is a vast category which includes lodging, food and drink service, event planning, theme parks, travel and tourism. It includes hotels, tourism agencies, restaurants and bars. In this review I got to know that how hotel is maintaining guest experience in this pandemic and building the good value in the market. for my research I also conduct a online survey which shows that how employees of Radisson blu Kaushambi is doing their best to maintain the guest expectations and how much they are satisfied working in this situation.
Keywords: covid; guest satisfaction; employees; staff; hospitality